2014
DOI: 10.1016/j.foodres.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' acceptance of a high-polyphenol yerba mate/black currant beverage: Effect of repeated tasting

Abstract: 24 25 26 27 28 29 30 31 32 33 34 35 36The effect of repeated tasting may improve the acceptance level and positive emotions associated with an unusual food. Our aim was to analyze this effect on the consumer acceptance, emotional status, purchase intention and optimum level of sensory attributes of a yerba mate (YMI)/black currant (BC) drink with high polyphenol content and low palatability.Beverages formulations (%) were: YMI 50 / BC 30 (S1); YMI 60 / BC 20 (S2); YMI 60 / BC 20/ diet sweetener 0.05% (S3). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Results are presented in Table and showed that the sucrose chocolate dessert received most of the high hedonic scores and that most consumers like this sample because of the appearance, but it not differed statistically ( P > 0.05) from the low sugar samples with sucrose, sucralose, aspartame, and stevia. As the main function of the sucrose is proportionate the sweet taste, our findings confirm previous studies (Esmerino and others ; Morais and others 2013; Paixão and others ; Orjuela‐Palacio and others ) indicating that the sweetness is highly related to overall linking of the processed product.…”
Section: Resultssupporting
confidence: 92%
“…Results are presented in Table and showed that the sucrose chocolate dessert received most of the high hedonic scores and that most consumers like this sample because of the appearance, but it not differed statistically ( P > 0.05) from the low sugar samples with sucrose, sucralose, aspartame, and stevia. As the main function of the sucrose is proportionate the sweet taste, our findings confirm previous studies (Esmerino and others ; Morais and others 2013; Paixão and others ; Orjuela‐Palacio and others ) indicating that the sweetness is highly related to overall linking of the processed product.…”
Section: Resultssupporting
confidence: 92%
“…Rinnan et al (2015) have indicate that, although CA is by far the most common analytical tool applied in this type of response data, the model does not contain any information regarding the uncertainty in the different attributes (which accounts for a large part of the data variation). These terms were mentioned with similar frequency for several samples, so they are situated near the coordinate centre (Orjuela-Palacio et al, 2014). But, as the noisy part of the data is large, the explained variation could seem to be rather low.…”
Section: Aroma Evaluationmentioning
confidence: 93%
“…Lemonade with mate was the least preferred in terms of sweetness. Yerba mate infusions had a bitter taste and astringency sensation that elicited negative consumer reactions when taken at high intensities (Jaeger et al, 2009;Lesschaeve & Noble, 2005;Drjuela-Palacio et al, 2014). Lemonade with linden or ginger and the control sample were the most attractive in terms of astringency.…”
Section: Sensory Analysesmentioning
confidence: 99%